Are Vegan Alternatives to Meat Products Healthy? A Study on Nutrients and Main Ingredients of Products Commercialized in Brazil - Romão, Bernardo; Botelho, Raquel Braz Assunção; Nakano, Eduardo Yoshio; Raposo, António; Han, Heesup; Vega-Muñoz, Alejandro; Ariza-Montes, Antonio; Zandonadi, Renata Puppin (Frontiers in Public Health, 2022)
Proteins are essential components in human nutrition, and animal products are usually the primary sources of human ingestion. However, the number of adherents to vegetarian and vegan diets has grown significantly, highlighting the need for alternatives to replace animal proteins. Meat substitutes aim to mimic the nutritional value and sensory characteristics of meat. However, studies suggest differences in their composition. This study is the first to evaluate Brazilian meat substitutes' nutritional quality and ingredients. A quantitative cross-sectional survey was performed in three steps: (i) Sample mapping of products commercialized nationwide; (ii) Ingredients and nutritional data collection and classification; (iii) Statistical analysis. One hundred twenty-five meat substitutes were included and described. The primary protein sources were soy, gluten, and pea protein ingredients. Vegan meat substitutes presented similar energy and protein values, with few exceptions among samples, with vegan canned fish alternatives presenting less protein than their counterparts. Overall vegan products did not differ regarding sodium levels but showed high amounts to compose a lunch or dinner meal. Vegan meat substitutes showed higher carbohydrates, dietary fiber concentrations, and few differences regarding total and saturated fat. Vegan meat substitutes may contribute to the adherence and maintenance of vegan and vegetarian diets. However, future studies about the implemented ingredients are needed.